The fintastic fishsitter a big fat zombie goldfish adventure - Jagucki, Marek (Feiwel & Friends, 2016)
"When Sami agrees to zombie-sit Frankie, her neighbor's big fat zombie goldfish, she is looking forward to fun afternoon in the paddling pool with her favorite "swishy fishy." Unfortunately, Fang, the mostly-evil vampire kitten, has a different idea. She's looking forward to a big fat zombie goldfish snack!"--Excerpt from Amazon.com